Controlled experiments measuring personal exposure to PM2.5 in close proximity to cigarette smoking. (2nd August 2013) - Acevedo‐Bolton, V.; Ott, W. R.; Cheng, K.‐C.; Jiang, R.‐T.; Klepeis, N. E.; Hildemann, L. M.
Abstract Few measurements of exposure to secondhand smoke (SHS) in close proximity to a smoker are available. Recent health studies have demonstrated an association between acute (<2 h) exposures to high concentrations of SHS and increased risk of cardiovascular and respiratory disease. We performed 15 experiments inside naturally ventilated homes and 16 in outdoor locations, each with 2–4 non‐smokers sitting near a cigarette smoker. The smoker's and non‐smokers' real‐time exposures to PM2.5 from SHS were measured by using TSI SidePak monitors to sample their breathing zones. In 87% of the residential indoor experiments, the smoker received the highest average exposure to SHS, with PM2.5 concentrations ranging from 50–630 μg/m3. During the active smoking period, individual non‐smokers sitting within approximately 1 m of a smoker had average SHS exposures ranging from negligible up to >160 μg/m3 of PM2.5. The average incremental exposure of the non‐smokers was higher indoors (42 μg/m3, n = 35) than outdoors (29 μg/m3, n = 47), but the overall indoor and outdoor frequency distributions were similar. The 10‐s PM2.5 averages during the smoking periods showed great variability, with multiple high concentrations of short duration (microplumes) both indoors and outdoors.